Prevalence of frailty and its association with oral hypofunction in older adults: a gender perspective - Karla Cruz-Moreira; Ludwig Alvarez-Cordova; Carla González-Palacios Torres; Peter Chedraui; José Jouvin; José Juan Jiménez-Moleón; Rocío Barrios-Rodríguez (BMC, 2023)
Abstract Background Previous studies have indicated an association between oral hypofunction and frailty in community-dwelling older adults. However, this issue has not been evaluated in institutionalized older patients. We aimed to determine the prevalence of physical frailty in this particularly vulnerable group and evaluate its association with oral hypofunction, analyzing possible differences by gender. Methods This cross-sectional study was conducted in private and public care homes in Guayaquil (Ecuador) from January 2018 until December 2019. Participants were classified as robust, pre-frail, and frail according to the Fried's frailty phenotype. Oral hypofunction was defined as the presence of at least three positive items in the following list: poor oral hygiene, oral dryness, reduced occlusal force, decreased masticatory function, and deterioration of swallowing function. The relationships between frailty and oral hypofunction were analyzed using logistic regression models for the whole sample and stratified by gender. Statistical analyses were performed using STATA 15.0 software (Stata Corp. LP, College Station, TX, USA). Results Among the 589 participants analyzed (65% women), the median age was 72 years (interquartile range: 66-82). Pre-frailty and frailty were presented in 66.7% and 28.9% of them respectively. Weakness was the most frequent item (84.6%). There was a significant relationship between frailty and oral hypofunction in women. In the overall sample, the frequency of frailty was 2.06 times higher (95% CI 1.30-3.29) in patients with oral hypofunction, and this association was maintained in women (ORa: 2.18; 95% CI 1.21-3.94). Reduced occlusal force and decreased swallowing function were items significantly associated with the presence of frailty (ORa: 1.95; 95% CI 1.18-3.22 and ORa: 2.11; 95% CI 1.39-3.19, respectively). Conclusion The prevalence of frailty and pre-frailty was high among institutionalized older people and was associated with the presence of hypofunction, especially in women. Decreased swallowing function was the most strongly item associated with frailty.